Analisis Manajemen Risiko Sistem Informasi E-LKPJ pada Dinas Komunikasi dan Informatika Provinsi Jawa Timur - Dian Ayu Permatasari; Widhy Hayuhardhika Nugraha Putra; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Information technology is being use by many companies including goverment agencies. Organization which uses information technology should carry out risk management to prevent information system obstacle. Dinas Komunikasi dan Informatika Provinsi Jawa Timur developed an E-LKPJ system. E-LKPJ system is a means of making an accountability report to DPRD. Based on governor regulations East Java no 48 of 2015 clause 9 verse 3, to ensure operation of the Electronic Transaction and System, Dinas Kominfo to insure system security and electronic transactions, applies risk management, develops operational standards and procedures, solves access problems and conducts audit at least once a year. Therefore Dinas Komunikasi dan Informatika Provinsi Jawa Timur necessary to carry out risk management in the E-LKPJ system. The aim of this study is identify potential risks in E-LKPJ system using NIST SP 800-30 framework. This study used qualitative methods by interviews and observation. This study produced a descriptions of system threats that come from electricity, natural disasters, fires, internet networks, passwords, and human resources. Meanwhile, threat sources which have potential vulnerabilities are electricity, internet networks, password, and human resources. The results of this study were risk level assessment including human resources at a high risk level, password at a moderate risk level, and electricity and internet networks having at a low risk level.